Forms and methods of media interaction with the target audience - Markabaeva, Г.Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
Trillions of messages sent out daily have given people the opportunity to communicate with each other quickly, without leaving their homes. Given such an effective mean of communication, today it is impossible to hide any information from people. When the Internet only began to develop, local media underwent certain changes. The World Wide Web has demonstrated to society completely new methods and technologies of communication. The Internet became a place for earning money. With the rise of new communication channels, the number of information sources has also increased dramatically. Therefore, with the Internet development, the mass media is losing its monopoly in the information space. A vast variety of information that is available to a nowadays person, combined with the rapid and effective development of new tools, forces us to think more about marketing and means of promoting those media sources. The Internet has not only changed media consumption but also increased competition. The main goal of the mass media became to attract the attention of the public and users.